'A short time but a lovely little short time': Bereaved parents' experiences of having a child with spinal muscular atrophy type 1. (10th September 2015) - Higgs, Emily J; McClaren, Belinda J; Sahhar, Margaret AR; Ryan, Monique M; Forbes, Robin
Abstract : Aim: Spinal muscular atrophy (SMA) type 1 is a relatively common, untreatable and invariably fatal neuromuscular disorder of early childhood. Psychosocial care is vital in management of families affected by this disease. There are few studies examining the impact of having a family member with a neuromuscular disorder, and none describing parents' experiences of having a child with SMA type 1. This study explored parents' perspectives of having a child with SMA type 1, from diagnosis to bereavement, in order to inform clinical practice by identifying aspects most meaningful to parents and to aid development of support strategies. Methods: This qualitative study undertook thematic analysis of 11 in‐depth interviews with 13 bereaved parents of children with SMA type 1. Results: While individuals' experiences were unique, common themes emerging from the data include: experiencing shock and anticipatory grief, processing feelings of responsibility and helplessness, experiencing multiple losses including the loss of future reproductive freedom, feeling supported, regaining a sense of control by making decisions about the child's life and death, and finding peace in the dying process. Conclusion: These findings highlight the importance of a multidisciplinary approach to the care of such families, including psychosocial support beginning from the time of diagnosis and continuing to bereavement. We suggest areas for further exploration, with a goal to develop family‐centred and evidence‐based psychosocial care guidelines to complement the current Standards of Care for Spinal Muscular Atrophy.